Expression of the γ-phosphorylated histone H2AX in gastric carcinoma and gastric precancerous lesions - GUO, ZHONG (Oncol Lett, 2015)
The histone γH2AX is a marker of activated DNA damage that is overexpressed in various cancers and corresponding precursor lesions, indicating that γH2AX is a component in oncogenic transformation. The present study aimed to determine whether the immunohistochemical expression of γH2AX is involved in the progression between superficial gastritis (n=20), atrophic gastritis (n=24) and gastric carcinoma (n=79). There was no increase in γH2AX expression between superficial and atrophic gastritis, but there was a significant increase in γH2AX expression between these two conditions and gastric carcinoma (χ(2)=68.712; P<0.001). The expression of γH2AX in moderately-differentiated gastric adenocarcinoma (n=49) was evidently higher compared with poorly-differentiated gastric adenocarcinoma (n=26; χ(2)=14.241; P<0.01). Staining for γH2AX did not reveal a significant association between the expression of the histone and patient age, depth of invasion, lymph node metastasis or the tumor-node-metastasis stage of the gastric carcinoma. Overall, the present study demonstrated that enhanced γH2AX expression may be closely associated with gastric carcinoma, but is less likely to be involved in the genesis of gastric carcinoma.